1999
DOI: 10.1007/s100249900149
|View full text |Cite
|
Sign up to set email alerts
|

Extralobar Sequestration with Frequently Associated Congenital Cystic Adenomatoid Malformation, Type 2: Report of 50 Cases

Abstract: Extralobar pulmonary sequestration (ELS) represents a mass of pulmonary parenchyma separate from the normal lung. The coexistence of congenital cystic adenomatoid malformation (CCAM) in ELS has been reported. To define this association, the clinical, gross, and histologic features of 50 ELS cases were analyzed. The age at diagnosis varied from birth to 65 years with 24% of cases diagnosed prenatally and 61% (23/38) diagnosed within the first 3 months of life. Fifty-two percent of cases were in females and 48% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(99 citation statements)
references
References 9 publications
4
83
1
11
Order By: Relevance
“…Large alveolus-like structures are present between the cysts. In 50% of the cases, type II CCAM has been found to be associated with extralobar pulmonary sequestration [3]. Type III, accounting for 10%, forms a solid and bulky mass, composed of regularly spaced bronchiole-like structures separated by masses of alveolus-like structures lined by cuboidal epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large alveolus-like structures are present between the cysts. In 50% of the cases, type II CCAM has been found to be associated with extralobar pulmonary sequestration [3]. Type III, accounting for 10%, forms a solid and bulky mass, composed of regularly spaced bronchiole-like structures separated by masses of alveolus-like structures lined by cuboidal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described as a distinct pathological entity in 1949 by Ch’in and Tang [1]and classified according to histological criteria by Stocker et al [2, 3]in 1977. Its etiology and pathogenesis remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary sequestration with CCAM has recently been reported more frequently in pediatric surgery [24]. Due to the presence of a mediastinal tumor with a cystic mass in the lung, a sequestration was also suspected in this patient.…”
Section: Discussionmentioning
confidence: 83%
“…Richard et al [2] reported that proportion of ELS with frequently associated congenital cystic adenomatoid malformation type II was approximately 50%. Recently, the pathogenesis of CCAM, LLS, ELS, and lobar emphysema has been thought to have common origins in different stages of lung development and at different sites and times, under the influence of airway obstruction [3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Smooth and striated muscle fibres are seen in types 1 and 2, respectively [4]. A coexistent CPAM type 2 has been reported in half of the patients with extralobar sequestration (ELS) [6], however the separation from the lung and the presence of a systemic blood supply are helpful to distinguish between these entities [3]. Type 4 lesions contain large cysts lined with flat alveolar cells, some of which contain surfactant [7].…”
Section: Congenital Pulmonary Airway Malformation (Cpam)mentioning
confidence: 99%